M2/M3 Bradley at war - Green, Michael, 1952-; Brown, James D. (Zenith Press, 2007)
If ever there were an armored fighting vehicle that today's soldier could love, it would be the Bradley: of 2,200 that muscled through Operation Desert Storm, only three were disabled. In a full-scale, fully detailed look at the M2/M3 Bradley Fighting Vehicle System, Michael Green, veteran writer on military machines and tour guide at a tank museum, and co-author James D. Brown conduct readers through the nuts and bolts, production history, and wartime work of the stalwart Bradley.